The effects of element diffusion on the pulsational properties of variable DA white dwarf stars - Córsico, Alejandro Hugo (2002)
We explore the effects of element diffusion due to gravitational settling and thermal and chemical diffusion on the pulsational properties of DA white dwarfs. To this end, we employ an updated evolutionary code coupled with a pulsational, finite difference code for computing the linear, non-radial g-modes in the adiabatic approximation. We follow the evolution of a 0.55-M⊙ white dwarf model in a self-consistent way with the evolution of chemical abundance distribution as given by time-dependent diffusion processes. Results are compared with the standard treatment of diffusive equilibrium in the trace element approximation. Appreciable differences are found between the two employed treatments. We conclude that time-dependent element diffusion plays an important role in determining the whole oscillation pattern and the temporal derivative of the periods in DAV white dwarfs. In addition, we discuss the plausibility of the standard description employed in accounting for diffusion in most white dwarf asteroseismological studies.